Preparation and characterization of Al2O3-25 mol% ZrO2composites - A. Rittidech (2018)
Al2O3-ZrO2(AZx), with 25 mol% ZrO2content, was prepared using the co-precipitation method. Synthesized powders were characterized by thermal reaction using a differential thermal analysis technique (TG-DTA) and were investigated by phase formation using X-ray diffraction. It indicated that the reaction occurred at 850°C; cubic (c)-ZrO2phase and Al2O3were obtained. By increasing temperature to 1100°C, tetragonal (t)-ZrO2phase was detected. The Al2O3-25 mol% ZrO2was sintered for 2 h in the temperature range of between 1300 and 1600°C. The majority phases of ceramics were m-ZrO2and α-Al2O3, although a t-ZrO2phase also appeared as a minor phase and decreased with higher temperature. Moreover, morphology and particle size evolution have been determined via the SEM technique. SEM showed that the particles of powder are agglomerated and basically irregular in shape. An SEM micrograph of ceramics exhibits uniform microstructure without abnormal grain growth. © 2011 Elsevier Ltd and Techna Group S.r.l.